2006
DOI: 10.1099/vir.0.81586-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of swine Torque teno virus in post-weaning multisystemic wasting syndrome (PMWS)-affected and non-PMWS-affected pigs in Spain

Abstract: The present study was designed to investigate the prevalence of swine Torque teno virus (TTV) in post-weaning multisystemic wasting syndrome (PMWS)-affected and non-affected Spanish swine. Nested PCR (nPCR) assays to detect two distinct TTV genogroups were applied. A significantly higher prevalence of TTV infection was found in sera from PMWS-affected animals (97 %) than in sera from non-PMWS-affected animals (78 %). Whilst PMWS-affected pigs (91 %) were more likely to be infected with TTV from genogroup 2 tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
146
3
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(169 citation statements)
references
References 19 publications
(31 reference statements)
6
146
3
6
Order By: Relevance
“…It is believed that TTVs might influence the development of some diseases or even modulate the outcome of disease by being present in blood or tissues (Okamoto, 2009). Even a clear-cut pathogenic role for TTSuVs has not been demonstrated to date, its role during co-infection with other pathogens is under debate, especially with regards to porcine circovirus diseases (PCVDs) (Ellis et al, 2008;Kekarainen et al, 2006;Taira et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that TTVs might influence the development of some diseases or even modulate the outcome of disease by being present in blood or tissues (Okamoto, 2009). Even a clear-cut pathogenic role for TTSuVs has not been demonstrated to date, its role during co-infection with other pathogens is under debate, especially with regards to porcine circovirus diseases (PCVDs) (Ellis et al, 2008;Kekarainen et al, 2006;Taira et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To check the detection limit of qPCR and compare the results, previously published nPCR methods for amplification of 39UTR of each TTV genogroup were used. 9 Nested PCR for TTV and PCR for PCV-2 were carried out with a commercial PCR kit. d Briefly, 1 ml of DNA, 1 ml of each primer of 10 pmol concentration, and 17 ml of DEPC-treated distilled water were mixed into a premix tube containing 2.5 U of Taq polymerase, 2.5 mM of each dNTP, 13 reaction buffer, and 13 gel loading buffer.…”
mentioning
confidence: 99%
“…TTSuV1 and TTSuV2 (TTSuVs) have been detected from serum, plasma, semen, faeces, colostrum, nasal secretion and various tissues [5,8,13,26,29,30] exclusively by Polymerase chain reaction (PCR), and different pig rearing countries have reported prevalence rate ranging from 24 to 100% [4,8,[14][15][16][17][24][25][26]. Limited longitudinal studies employing serum [17,26] and cross-sectional studies employing serum and tissues [1,8,9,27] have shown that TTSuV infection increases with age.…”
mentioning
confidence: 99%
“…Limited longitudinal studies employing serum [17,26] and cross-sectional studies employing serum and tissues [1,8,9,27] have shown that TTSuV infection increases with age. However, little is known about primary infection with TTSuV and sites of viral persistence and reactivation after infection in the pigs, and to the best of our knowledge there is no report on the detection of TTSuVs in peripheral blood mononuclear cells (PBMCs) in pigs.…”
mentioning
confidence: 99%
See 1 more Smart Citation